Studies on Complexes of Nickel(II) and Copper(II) with Ampicillin - Guru, Pranay (Asian Journal of Chemistry, 2010)
Ni(II) and Cu(II) complexes with ampicillin with the general formula M(C16H19N3O4S)WO4×4H2 O (M=Ni or Cu) have been synthesized and characterized on the basis of elemental analysis and molar conductance. The geometries of the complexes have been investigated by magnetic, electronic and infrared spectral data. TGA studies have also been carried out to know the pattern of their decomposition.